2014
DOI: 10.5194/hess-18-1561-2014
|View full text |Cite
|
Sign up to set email alerts
|

Selection of intense rainfall events based on intensity thresholds and lightning data in Switzerland

Abstract: Abstract. This paper presents a method to identify intense warm season storms with convective character based on intensity thresholds and the presence of lightning, and analyzes their statistical properties. Long records of precipitation and lightning data at 4 stations and 10 min resolution in different climatological regions in Switzerland are used. Our premise is that thunderstorms associated with lightning generate bursts of high rainfall intensity. We divided all recorded storms into those accompanied by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 62 publications
3
47
1
Order By: Relevance
“…might allow us to have a better understanding of the whole hydrological regime which could be used to more accurately sort the database. For example, a recent study by Gaál et al (2014) suggested the use of lightning data as an indicator of convectivity in rainfall events. Additionally, there are other climatic indicators related to the energy and water balance, such as the aridity index (ratio between potential evapotranspiration and mean annual precipitation), that could provide together with rainfall and temperature valuable information on the climate type.…”
Section: Discussionmentioning
confidence: 99%
“…might allow us to have a better understanding of the whole hydrological regime which could be used to more accurately sort the database. For example, a recent study by Gaál et al (2014) suggested the use of lightning data as an indicator of convectivity in rainfall events. Additionally, there are other climatic indicators related to the energy and water balance, such as the aridity index (ratio between potential evapotranspiration and mean annual precipitation), that could provide together with rainfall and temperature valuable information on the climate type.…”
Section: Discussionmentioning
confidence: 99%
“…These are all 10 min precipitation depths, with 0.1 mm resolution, measured over the exact same period with the same Lambrecht tippingbucket instruments, with standardized calibration and maintenance. These rainfall data are of very good quality and have recently been used in other studies of storm properties in Switzerland (e.g., Gaál et al, 2014;Molnar et al, 2015).…”
Section: Study Sites and Datamentioning
confidence: 99%
“…Although there are many different approaches for selecting a criterion for event independence (e.g., Dunkerley, 2008), we chose to discriminate successive independent storms based on a minimum inter-event time, MIT (Restrepo-Posada and Eagleson, 1982;Driscoll et al, 1989;Gaál et al, 2014). With this scheme, any dry spell (i.e., between recorded precipitation) longer than the MIT defines two independent storms.…”
Section: Event Definitionmentioning
confidence: 99%
“…Precipitation is a major cause of natural hazards and is related to flooding [1][2][3]. The severity of a precipitation event and its potential damage is dependent on the total amount of rain and also on its intensity and duration [1].…”
Section: Introductionmentioning
confidence: 99%